Explanatory Study of Student-Teacher Interactions, Students’ Academic Motivation, and Teacher’s Motivation in English Classes - Putri, Stephanie Priyanto; Pratama, Hendi; Fitriati, Sri Wuli (Soegijapranata Catholic University, 2023)
This study aims to determine the relationship between student-teacher interaction, students' academic motivation, and the teacher's motivation in the eighth-grade English classroom. Quantitative and qualitative data on student-teacher interaction and academic motivation in English learning were collected using a questionnaire, observation, and interview. 137 eighth-grade students at Semarang's Karangturi junior high school in the academic year 2022-2023 were the subjects of this study. Using an observation sheet from Ottevanger (2001), it was determined to see to what extent the teacher uses student-teacher interaction to increase students' and teachers' academic motivation. A final interview is conducted with the English teacher to determine her perception of student-teacher interaction. The results demonstrate a correlation between student-teacher interaction and students’ academic motivation in English classes. The instructor utilizes these interactions by posing questions and issuing directives. Moreover, the instructor concurred that student-teacher interactions are highly beneficial for both students and instructors.